The Employment Dynamics of Disadvantaged Women: Evidence from the SIPP - Ham, John C.; Li, Xianghong; Shore-Sheppard, Lara D. (Journal of Labor Economics, 2016)
Understanding the employment dynamics of disadvantaged families is increasingly important. We estimate duration models describing these dynamics for disadvantaged single mothers and use them to conduct a rich set of counterfactual analyses. We use a misreporting model to correct for “seam bias,” the problem that too many transitions are reported between reference periods in panel data. We find effects of demographics, minimum wages, unemployment rates, and maximum welfare benefits, but not policy changes introduced through state welfare waivers, on employment dynamics. We find that two commonly used ad hoc methods of addressing seam bias perform substantially worse than our approach.